2008
DOI: 10.1136/oem.2008.039081
|View full text |Cite
|
Sign up to set email alerts
|

The virtues of a deliberately mis-specified disease model in demonstrating a gene-environment interaction

Abstract: If "gene" contributes to disease risk only in the presence of exposure, the existence of the gene-environment interaction can be efficiently inferred from a deliberately mis-specified "gene-only" disease model in nested case-control studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In the analysis of gene–environment effect modification, statistical power becomes an even greater issue as studies typically require large sample sizes to detect effect modification 28. It has been demonstrated that even small errors in the assessment of environmental factors can result in biased interaction parameters and substantially increased sample size requirements for the detection of effect modification 6 7. In our analyses, misclassification of exposure by the JEM as compared to expert assessment resulted in smaller ORs and less likelihood of detecting an effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of gene–environment effect modification, statistical power becomes an even greater issue as studies typically require large sample sizes to detect effect modification 28. It has been demonstrated that even small errors in the assessment of environmental factors can result in biased interaction parameters and substantially increased sample size requirements for the detection of effect modification 6 7. In our analyses, misclassification of exposure by the JEM as compared to expert assessment resulted in smaller ORs and less likelihood of detecting an effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that even small errors in the assessment of environmental factors can result in biased estimates of interaction parameters and substantial decreases in study power 6 7. Also, unless we use the most accurate exposure assessment methods in studies evaluating genotypes and environmental exposures, there is a greater probability of detecting associations with genotypes rather than environmental exposures, since genotyping typically has a lower degree of classification error 8…”
Section: Introductionmentioning
confidence: 99%
“…A slightly different issue, but one that shares some similarities, is how under some conditions gene-only models often more reliably indicate the presence —if not precise magnitude —of a gene–environment interaction than a model with an environmental exposure and gene-by-environment interaction term, in part because only including the gene term avoids potential confounding bias from variables that confound the environmental exposure–outcome association. 47,48 …”
Section: Potential Epidemiologic Advantages Of Proxy Measuresmentioning
confidence: 99%
“…Inclusion of frequency or duration of use of pesticides in cumulative exposure indices could introduce further misclassification that would typically lead to under-estimates of risk, as has been shown elsewhere. 21 On the other hand, it is also possible that recall of the details of pesticide use over many growing seasons might provide a better estimate of cumulative exposure over a long time period than a biological measurement of exposure from a single application, particularly because urinary levels from non-persistent pesticide exposure reflect only recent use and are not necessarily a measure of long-term use.…”
Section: Discussionmentioning
confidence: 99%